2014
DOI: 10.1002/cctc.201402581
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nanointerfaces in Cu‐ and Cu+Au‐Based Near‐Ambient‐Temperature CO Oxidation Catalysts

Abstract: Disordered mesoporous Cu‐doped ceria‐zirconia (Cu0.1Ce0.85Zr0.05O2), and gold deposited (Au/Cu0.1Ce0.85Zr0.05O2) catalysts were synthesized and evaluated for CO oxidation. Onset of CO oxidation activity, and 50 % (100 %) CO2 formation occurs at room temperature (RT), and 77 (120)°C, respectively, with Cu0.1Ce0.85Zr0.05O2. A small amount of gold on Cu0.1Ce0.85Zr0.05O2 induces the sustainable oxidation catalysis around RT. Onset of copper reduction temperature decreases from 110 °C on Cu0.1Ce0.85Zr0.05O2 to 48 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 92 publications
3
32
0
Order By: Relevance
“…Clearly, a distinct redshift and a small broadening of the F 2g band are observed on all the CuO/CeO 2 catalysts compared with support CeO 2 (466 cm -1 ). According to the literature [29], the reason of shifting and broadening of the F 2g band may be the presence of oxygen vacancies, which is related to structural defects derived from partial incorporation of copper into the ceria lattice, in good agreement with the decrease of lattice parameter microstrain values as shown in Table 1.…”
Section: Raman Analysissupporting
confidence: 72%
See 1 more Smart Citation
“…Clearly, a distinct redshift and a small broadening of the F 2g band are observed on all the CuO/CeO 2 catalysts compared with support CeO 2 (466 cm -1 ). According to the literature [29], the reason of shifting and broadening of the F 2g band may be the presence of oxygen vacancies, which is related to structural defects derived from partial incorporation of copper into the ceria lattice, in good agreement with the decrease of lattice parameter microstrain values as shown in Table 1.…”
Section: Raman Analysissupporting
confidence: 72%
“…However, when the CuO loading is higher than 10 wt%, the peak, respectively, shifts from 455 cm -1 for 10-CC to 457 cm -1 for 15-CC and 459 cm -1 for 25-CC, and the band width decreases slightly. This result suggests that the amount of oxygen vacancies increases first and then decreases with the increase in CuO content, i.e., the 10-CC sample has the largest amount of oxygen vacancies [29].…”
Section: Raman Analysismentioning
confidence: 89%
“…It was noted that the XRD peaks of CeO 2 became broader and the relative peak intensity became weaker with the increase of Cu loading. This result indicates that the addition of Cu can suppress the sintering of Ce-Zr-O solid solution during the calcination process [20], which was verified by their smaller particle sizes determined by Scherrer equation as shown in Table 1. It was reported that Cu 2+ (0.072 nm) could substitute Ce 4+ (0.097 nm) into the CeO 2 cell and reduce the CeO 2 cell size [4].…”
Section: Resultsmentioning
confidence: 57%
“…1. This result suggests that the Cu species mainly exist as highly dispersed states on the support surface which cannot be detected by the XRD instrument, or as a Cu-Ce-Zr-O solid solution or a combination of the two phenomena [20,[22][23][24]. Comparatively, evident diffraction lines of CuO appear at 2u of 35.6 and 38.88 for the 33-CCZ sample, indicating that the presence of bulk CuO should be ascribed to the aggregation of excessive CuO species on the support surface.…”
Section: Resultsmentioning
confidence: 95%
“…It is found that the surface concentrations of Cu and Ce on all the catalyst are much lower than their nominal concentrations (5 wt% and 20 wt%, respectively), but increase progressively with increasing of PEG contents. This phenomenon can be attributed to two reasons: 25,26,31 (1) the components in the mesopores of the support SBA-15 may not be detected because of the shielding of silica skeleton; (2) as the content of PEG in the impregnating solution is increased, the components are easier to deposit on the external surface of SBA-15 carrier.…”
Section: Xps Studymentioning
confidence: 99%